2010
DOI: 10.1073/pnas.0914643107
|View full text |Cite
|
Sign up to set email alerts
|

bZIP transcription factor zip-2 mediates an early response to Pseudomonas aeruginosa infection in Caenorhabditis elegans

Abstract: Very little is known about how animals discriminate pathogens from innocuous microbes. To address this question, we examined infection-response gene induction in the nematode Caenorhabditis elegans. We focused on genes that are induced in C. elegans by infection with the bacterial pathogen Pseudomonas aeruginosa, but are not induced by an isogenic attenuated gacA mutant. Most of these genes are induced independently of known immunity pathways. We generated a GFP reporter for one of these genes, infection respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
169
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(189 citation statements)
references
References 29 publications
11
169
1
Order By: Relevance
“…4C). Consistent with this, ZIP-2-dependent genes (19) were up-regulated in liquid killing (Fig. 4D).…”
Section: Elegans Uses a Multifaceted Innate Immune Response To Liquidsupporting
confidence: 72%
See 1 more Smart Citation
“…4C). Consistent with this, ZIP-2-dependent genes (19) were up-regulated in liquid killing (Fig. 4D).…”
Section: Elegans Uses a Multifaceted Innate Immune Response To Liquidsupporting
confidence: 72%
“…The bZIP transcription factor ZIP-2 also plays a key role in defense against P. aeruginosa infection (19). ZIP-2 is also known to be activated by damage-associated molecular patterns, including translational inhibition and mitochondrial disruption (20,21), which suggests that ZIP-2 may bridge the divide between immunity and stress response genes.…”
Section: Elegans Uses a Multifaceted Innate Immune Response To Liquidmentioning
confidence: 99%
“…Several conserved transcription factors including GATA/ELT-2 (1), FOXO/DAF-16 (15), and bZIP/ZIP-2 (32) regulate the expression of immunity-related genes and protect C. elegans from lethal infection by P. aeruginosa (1,32). We found that disruption of ELT-2 rendered worms hypersusceptible to B. pseudomallei infection, indicating that ELT-2 also protects C. elegans from a lethal B. pseudomallei infection.…”
Section: Discussionmentioning
confidence: 79%
“…elegans Strains and Maintenance. N2-Bristol, Phsp-4::GFP, Phsp-6::GFP, Pgst-4:: GFP (acquired from the Caenorhabditis Genetics Center); PF35E2.5, Pclec-60::GFP, Pirg-1::GFP (gifts from F. Ausubel, Massachusetts General Hospital, Boston) (39)(40)(41). All strains were maintained on NGM plates (no antibiotics) spotted with E. coli OP50 at 20°C-22°C using standard protocols (42) unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%